La consigne est toujours la même mettre(x-1) en facteur puis réduire le deuxième facteur.
7(x-1)(2x+1)-2(x-1)(3x-4)
3(x-5)(x-1)+4x-4
2(x+8)(x-1)+x-1
(X-1)(x+1)+(6x-7)(3x-3)
4
X -1
(X-1)(x+8)-x+1
(X-1)(5x+9)+(4x-7)(-3x+3)
Merci

1
4
X -1
sont sur la meme ligne?
oui mais nan

Réponses

2014-01-11T10:59:49+01:00
7(x-1)(2x+1)-2(x-1)(3x-4)
=(x-1)(14x+7-6x+8)
=(x-1)(8x+15)

3(x-5)(x-1)+4x-4
=3(x-5)(x-1)+4(x-1)
=(x-1)(3x-15+4)
=(x-1)(3x-11)

2(x+8)(x-1)+x-1
=2(x+8)(x-1)+(x-1)
=(x-1)(2x+16+1)
=(x-1)(2x+17)

(X-1)(x+1)+(6x-7)(3x-3)
=(x-1)(x+1)+(6x-7)3(x-1)
=(x-1)(x+1+18x-21)
=(x-1)(19x-20)

(X-1)(x+8)-x+1
=(x-1)(x+8)-(x-1)
=(x-1)(x+8-1)
=(x-1)(x+7)

(X-1)(5x+9)+(4x-7)(-3x+3)
=(x-1)(5x+9)-3(4x-7)(x-1)
=(x-1)(5x+9-12x+21)
=(x-1)(-7x+30)